The Role of Arabic Language Teachers in Utilizing Educational Technology Using Applications (هالو العربية ) in MI Assalafiyah Cibiuk - Tiara Aminatusshalihah; Machmud Yunus; Syarifah Aini (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The aims to of this research determine the extent of the role of Arabic teachers in utilized educational technology in Madrasah Ibtidaiyah Assalafiyah Cibiuk, researchers used learning media such as applications. The result of this research qualitative design methods, while the data collection techniques used are Observation, Interview, Questionnaire, Sampling, and Documentation Study techniques. The results of this study revealed that the Arabic learning process is effectively carried out with a variety of learning models that are not monotonous, in other words, learning using application media helps students understand the learning delivered. With a variety of learning models and android applications used, reinforcement to enhance the teaching experience and intended for Arabic language education to assist teachers and parents in providing Arabic understanding to students both at school and at home.